Traumatic brain injuries in Aotearoa New Zealand adolescents: Health inequity pathways from upstream factors to downstream causes - Angad S. Chauhan (New Zealand Medical Student Journal, 2023)
Traumatic brain injuries are socially patterned in Aotearoa, with males, Māori, Pasifika, rural, and adolescent populations experiencing disproportionately higher rates. These inequitable health outcomes may be attributed to various risk factors that either increase exposure to dangerous settings or promote high risk-taking behaviour. These factors are driven by upstream social determinants including colonisation, institutional racism, law enforcement agencies, government, socio-economic status (SES), and cultural environment.